COMMUNICATION INSTRUCTIONAL - Muhammad Joharis Lubis (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2015)
Instructional communication is the process of moving some messages(knowledge) educators to learners. Course material will be digested well, if thematerial presented can be interpreted equally by learners as contemplated byeducators.